UPAYA MENINGKATKAN HASIL BELAJAR GERAK SENAM RITMIK MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIVE TIPE JIGSAW SISWA KELAS V SDN 3 SUKAJAWA BANDAR LAMPUNG - Sulasmini Sulasmini (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
The purpose of this study was to improve the quality of learning including teacher skills, student activities and learning outcomes of rhythmic gymnastics for fifth grade students of SDN 3 Sukajawa. This type of research is a classroom action research with two cycles. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The research subjects were students of class V SDN 3 Sukajawa. Data collection techniques used knowledge tests, performance tests and attitude tests. The results showed that the skills of the first cycle teachers obtained an average score of 70 with good criteria. In the second cycle obtained an average score of 80 with very good criteria. The level of knowledge of the first cycle students obtained an average score of 77.8 with good criteria. Cycle II increased with an average score of 82.4 with very good criteria. The results of student performance in the first cycle obtained an average score of 74.5 while the second cycle obtained an average score of 81.6. The final score in cycle I obtained a score of 70 and in cycle II increased to 85. Completeness of classical learning cycle I was 72.2%, cycle II increased to 83.3%.